Urinary catheterization in gynecological surgery: When should it be removed? (Medical Journal of Indonesia, 2013)
Background: The aim of this study was to determine the most appropriate time for urinary catheter removal following a gynecological surgery.Methods: Critical appraisal of clinical trial articles were conducted. It was aimed to answer our clinical question whether 24-hour postoperative urinary catheter removal is superior compared to other durations in avoiding postoperative urinary retention (PUR) and urinary tract infection (UTI). The search was conducted on the Cochrane LibraryÂ® and PubMedÂ® using keywords âpostoperative urinary retentionâ, âpostoperative catheterizationâ and âurinary retention AND catheterizationâ. Reference lists of relevant articles were searched for other possibly relevant trials.Results: Seven articles were available as full text, then appraisals of six prospective RCTs involving 846 women underwent hysterectomy and vaginal prolapse surgery were performed finding at the re-catheterization and UTI rate. Subjects in earlier-removal groups were 3 to 4 times more likely to have re-catheterization (OR = 3.10-4.0) compared to later-removal groups, while they who have it removed on 5th day were 14 times more likely to develop UTI compared with immediate group (OR = 14.786, 95% CI 3.187- 68.595).Conclusion: The 24-hour catheterization policy in hysterectomy and vaginal prolapse surgery remains most appropriate although associated with an increased risk of re-catheterization. The removal of catheter before 24 hour (6 or 12 hour) could be considered to be used as one of interventions in further RCT(s) to find out the best duration which would result in lowest incidence in both of UTI andÂ  PUR. (Med J Indones. 2013;22:183-8. doi: 10.13181/mji.v22i3.589)Keywords: Catheter, hysterectomy, prolapse, urinary tract infection